Glymphatic Drainage Blocking Aggravates Brain Edema, Neuroinflammation via Modulating TNF-α, IL-10, and AQP4 After Intracerebral Hemorrhage in Rats - Liu, Xichang; Wu, Gang; Tang, Na; Li, Li; Liu, Cuimin; Wang, Feng; Ke, Shaofa (Frontiers in Cellular Neuroscience, 2021)
Objective: The “Glymphatic” system, a network of perivascular tunnels wrapped by astrocyte endfeet, was reported to be closely associated with the diseases of the central nervous system. Here, we investigated the role of the glymphatic system in intracerebral hemorrhage (ICH) and its protective mechanism. Method: Experimental ICH model was induced by type IV collagenase in rats. Cerebral lymphatic blockage was induced by ligation and removal of cervical lymph nodes. The experimental rats were divided into sham-operated (SO) group, ICH group, and cerebral lymphatic blocking and ICH (ICH + CLB) group. Neurological scores were measured using the Garcia scoring system on the third and seventh day after ICH. Active caspase-3 was immunostained to evaluate neuronal apoptosis. Brain water content was calculated using the dry-wet specific gravity method. The expression of inflammatory factors TNF-α, IL-1β, and IL-10 were detected using ELISA. Aquaporins-4 (AQP-4) and glial fibrillary acidic protein (GFAP) were detected using western blot analysis. Results: The neurological scores of rats in the CLB + ICH group were significantly lower than those in the in ICH group. The number of active caspase-3 neurons was significantly higher in the CLB + ICH group compared to the ICH group. CLB significantly aggravated ICH-induced brain edema 3 d after ICH. There was an increase in the expression of TNF-α, IL-1β, IL-10, AQP-4, GFAP after ICH. The expression of TNF-α was significantly higher in the CLB + ICH group compared to ICH group 3 d after ICH while there was no difference 7 d after ICH. There was no statistical difference in the expression of IL-1β between the ICH group and CLB + ICH group. However, the expression of IL-10 in the CLB + ICH group was significantly lower than that in the ICH group. Lastly, AQP-4 expression was significantly lower in the CLB + ICH group compared to the ICH group while the expression of GFAP was higher in the CLB + ICH group compared to the ICH group. Conclusion: CLB exacerbated cerebral edema, neuroinflammation, neuronal apoptosis and caused neurological deficits in rats with ICH via down-regulating AQP-4, up-regulating inflammatory TNF-α and inhibiting IL-10 expression. The glymphatic drainage system protects against neurologic injury after ICH induction in rats under normal physiological conditions.